The 37/67kDa laminin receptor (LR) inhibitor, NSC47924, affects 37/67kDa LR cell surface localization and interaction with the cellular prion protein - Sarnataro, Daniela (Sci Rep, 2016)
The 37/67 kDa laminin receptor (LR) is a non-integrin protein, which binds both laminin-1 of the extracellular matrix and prion proteins, that hold a central role in prion diseases. The 37/67 kDa LR has been identified as interactor for the prion protein (PrP(C)) and to be required for pathological PrP (PrP(Sc)) propagation in scrapie-infected neuronal cells, leading to the possibility that 37/67 kDa LR-PrP(C) interaction is related to the pathogenesis of prion diseases. A relationship between 37/67 kDa LR and PrP(C) in the presence of specific LR inhibitor compounds has not been investigated yet. We have characterized the trafficking of 37/67 kDa LR in both neuronal and non-neuronal cells, finding the receptor on the cell surface and nuclei, and identified the 67 kDa LR as the almost exclusive isoform interacting with PrP(C). Here, we show that the treatment with the 37/67 kDa LR inhibitor, NSC47924, affects both the direct 37/67 kDa LR-PrP(C) interaction in vitro and the formation of the immunocomplex in live cells, inducing a progressive internalization of 37/67 kDa LR and stabilization of PrP(C) on the cell surface. These data reveal NSC47924 as a useful tool to regulate PrP(C) and 37/67 kDa LR trafficking and degradation, representing a novel small molecule to be tested against prion diseases.